The Effect of Islamic Corporate Governance, Firm Characteristic on Capital Structure and Financial Performance of Sharia Commercial Banks Registered the Financial Services Authority - Ferriswara, Dian; Karneli, Okta; Yusuf, Bibi Noraini Mohd (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
This study examines the relationship between Islamic corporate governance, firm characteristics on capital structure and financial performance in Islamic Commercial Banks. The data analysis technique uses Partial Least Square (PLS), with structural equations (SEM) based on components or variants, on annual data from 2017 to 2021. The findings show that three determinants significantly affect the financial performance of the five hypotheses proposed. Islamic corporate governance has a significant effect on financial performance in a negative direction, and a significant positive effect on capital structure Firm characteristic has no significant effect on capital structure and financial performance. Capital structure factors influence financial performance. The practical implications of this study emphasize the important role of the sharia supervisory board and independent commissioners in improving the financial performance of Islamic commercial banks